Strategies for developing effective information policies - Moore, Nick (ACURIL [S.l.], 1993)
Provides an analysis of information policy for the Caribbean. Identifies three different policy levels: industrial; organisational and social. At each of which there are four elements which need to be taken into account: information technology; information markets; human resources, and legislation and regulation. Shows how by combining the levels and elements it is possible to construct an information policy matrix which can be used to analyze the policy requirements of the Caribbean nations.